FEASIBILITY ANALYSIS OF CARP (Cyprinuscarpio) FARMING AND MARKETING IN SIMALUNGUN DISTRICT - Zul Fadhly; Retna Astuti Kuswardani; Endang Sari Simanullang (RADJA PUBLIKA, 2024)
The aim of this research isto analyze the income of carp farmers(Cyprinus carpio)in Simalungun Regency, to analyze the feasibility of goldfish farming(Cyprinus carpio)Simalungun Regency,.The sampling technique in this research was carried out using provocative sampling with categories: privately owned land, land area 1.5-2 ha. to 20 farmers each. Financial analysis methods, feasibility analysis, and efficient analysis with analysis of business costs, revenues and profits, break even point (BEP), R/C Ratio, B/C Ratio. The research results show that: Profits in Simalunngun Regency are averageRp.8,668,415per harvest The marketing efficiency of carp farming in Simalungun Regency is an average of 9.73%, so marketing is efficient.